2021
DOI: 10.1175/jpo-d-21-0023.1
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Parameterizations for Enthalpy and Momentum Fluxes from Sea Spray in Tropical Cyclones

Abstract: The intensity of tropical cyclones is sensitive to the air-sea fluxes of enthalpy and momentum. Sea spray plays a critical role in mediating enthalpy and momentum fluxes over the ocean’s surface at high wind speeds, and parameterizing the influence of sea spray is a crucial component of any air-sea interaction scheme used for the high wind regime where sea spray is ubiquitous. Many studies have proposed parameterizations of air-sea flux that incorporate the microphysics of sea spray evaporation and the mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 117 publications
0
13
0
Order By: Relevance
“…As such, it has an indirect, rather than direct, influence on the air-sea momentum flux. In addition to indirect dynamic effects, sea spray also directly influences the air-sea momentum, such as by modulating the roughness length [40,41] and increasing/decreasing the net air-sea momentum fluxes [42]. While it is still under debate how the sea spray dynamically affects the air-sea interaction, spray droplets strongly mediate net air-sea momentum fluxes, accounting for up to 16% of the interfacial momentum fluxes [43].…”
Section: Impacts On the Tc Systemmentioning
confidence: 99%
“…As such, it has an indirect, rather than direct, influence on the air-sea momentum flux. In addition to indirect dynamic effects, sea spray also directly influences the air-sea momentum, such as by modulating the roughness length [40,41] and increasing/decreasing the net air-sea momentum fluxes [42]. While it is still under debate how the sea spray dynamically affects the air-sea interaction, spray droplets strongly mediate net air-sea momentum fluxes, accounting for up to 16% of the interfacial momentum fluxes [43].…”
Section: Impacts On the Tc Systemmentioning
confidence: 99%
“…An accurate estimation of air-sea enthalpy and momentum fluxes is key to improving intensity forecast accuracy in numerical weather prediction models (Sroka and Emanuel, 2021). Whether C k /C d decreases or increases at extreme winds above 50 m s −1 remains debatable.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…One factor in particular that is central to our understanding of the transfer of heat and momentum at high wind speeds is the presence of spray droplets. Spray mediation of air-sea fluxes has been the subject of many previous investigations, including theoretical, observational, and numerical modeling approaches, and a comprehensive review on the subject can be found in Veron (2015) or Sroka and Emanuel (2021). Although many numerical modeling studies have investigated the impact of spray on air-sea fluxes, most of these studies have relied on bulk estimates in which the net effect of spray is parameterized rather than handled explicitly.Here we investigate the impact of sea spray on the transfer coefficients for momentum, heat, and moisture, by performing simulations using a large-eddy simulation (LES) code coupled with a Lagrangian microphysical model.…”
mentioning
confidence: 99%
“…Further complications arise from a lack of knowledge on how the presence of sea spray affects the air-sea fluxes, and how this varies with wind speed (Veron, 2015). Improving parameterizations of air-sea fluxes in numerical models is of particular importance for reducing uncertainty in intensity forecasts (Sroka & Emanuel, 2021).…”
mentioning
confidence: 99%